Improved Direct Torque Control Load Torque Estimator With The Influence Of Steering Angle For Dual Induction Motors Electric Vehicle Traction Drive System - Ibrahim, Zulkifilie; Mohd Yaakop, Nurazlin; Ahmad, Fauzi; Sulaiman , Marizan; Jusoff, Kamaruzaman; Jano, Zanariah; Linda , Khoo Mei Sui; Abu Hasim, Ahmad Shukri; Mat Isa, Siti Noormiza (IDOSI Publications, 2011)
-